SEKOLAH: MEMBERDAYAKAN ATAU MEMPERDAYA MASYARAKAT - Hamka Hamka (State Institute of Islamic Studies (IAIN) Palu, 2010)
Formal institution of education symbolized as “school” has been criticized by several experts since the last several decades. In one hand, this institution is judged to fail to do its tasks, both in forming the morality of the students and in transforming knowledge and skill needed by society. In other hand, this institution is judged as only a tool to legitimate class domination over inferior class. There are several solutions offered by experts, but the most realistic one is to do reformation in the side of the system of education focusing on the substance rather than on formality. And the very important thing to do is to change the paradigm of the society towards the school itself.Kata Kunci: sekolah, pendidikan, kurikulum, masyarakat